The Family Characteristics, Eight Family Functions and Socio-Economic Class of Contribution Assistance Recipient Families in Indonesia - Sugiharto, Adam; Riany, Yulina Eva (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2024)
Efforts to realize quality human and family resources can be achieved through optimizing the implementation of the eight family functions. This research was conducted to analyze what kind of family characteristics and at what socio-economic level are the families receiving contribution assistance in Indonesia, as well as to examine the extent of knowledge about the eight functions of the family in families receiving contribution assistance. This study uses longitudinal secondary data from the 2015-2019 National Medium-Term Development Plan Performance Indicator Survey. Data processing and analysis were carried out descriptively and inferentially using cross tabulation and regression testing. The study included 943,004 individual respondents. The result show that the higher the socioeconomic class of the family, the higher the knowledge about the eight family functions, this is statistically very significant as evidenced by the P value below 0.05, with a coefficient of 0.676. It is surprising that this study states that family size has no significant effect on socioeconomic class. Study proves that when the PBI Contribution recipient family data is regressed with socioeconomic class, the low economic class is positively correlated with a coefficient value of 0.481 and is statistically significant with a 95 percent confidence level and below 0.05, which is 0.000, meaning that in low socioeconomic families, they are the largest recipients of PBI contributions.